Are mobile phones safe?. - Foster, K.R (IEEE spectrum)
Driven in part by disturbing allegations, a new wave of research in the United States and elsewhere is exploring possible links between cell phone radiation and cancer. Brain cancer, the topic of this article, is not the only health concern, but it dominates public discussion. A substantial body now exists of pertinent scientific evidence. This article discusses EM fields and research on looking for a link between them and cancer. The results of animal studies are briefly outlined. The article discusses exposure limits to RF radiation